Expanded Screening of One Million Swedish Babies with R4S and CLIR for Post-Analytical Evaluation of Data - Lene Sörensen; Ulrika von Döbeln; Henrik Åhlman; Annika Ohlsson; Martin Engvall; Karin Naess; Carolina Backman-Johansson; Yvonne Nordqvist; Anna Wedell; Rolf H. Zetterström (MDPI AG, 2020)
Sweden has one neonatal screening laboratory, receiving 115 to 120 thousand samples per year. Among the one million babies screened by tandem mass spectrometry from November 2010 until July 2019, a total of 665 babies were recalled and 311 verified as having one of the diseases screened for with this methodology, giving a positive predictive value (PPV) of 47% and an incidence of 1:3200. The PPV was high (41%) already in the first year after start of screening, thanks to the availability of the collaborative project Region 4 Stork database. The PPV is presently 58%. This improvement was achieved by the implementation of second-tier analyses in the screening for methylmalonic aciduria, propionic aciduria, isovaleric aciduria, and homocystinuria, and the employment of various post analytical tools of the Region 4 Stork, and its successor the collaborative laboratory integrated reports.